Heroine: Srikandi Melayu Melaka (fiction) / Norazrin Che Adnan - Che Adnan, Norazrin (Faculty of Art and Design, 2020)
This project is based on novel 1515 by Faisal Tehrani, winner of the Utusan Group Literary Prize teen novel category in 2002.